The Effectiveness of Artificial Intelligence Multimedia in Subject Physics Mechanic for Diploma in Applied Science - Mohd Badri, Ahmad Faiz Hakimi; Morad, Nur Ain Akasya; Wan Abd Aziz, Wan Izzati Syafiqa; Nordin, Norbaizura (Multidisciplinary Applied Research and Innovation, 2025)
Physics Mechanics is a fundamental subject that is encompassed in the applied science diploma program. Many students encounter difficulties in grasping the core concepts of mechanics. This may be attributed to conventional teaching methods, complex learning materials, limited exposure to practical experiments, or a lack of hands-on experience in conducting experiments. This study aims to increase the percentage of students' understanding of physics mechanics by developing a Artificial Intelligence (AI) learning module. Sample of 90 students from the DAU students at UTHM Pagoh, consisting of first-year DAU (1DAU) batch 2023/2024, second-year batch DAU (2DAU) 2022/2023, and third-year batch DAU (3DAU)  2021/2020 students. Sample of 30 students from 2DAU as Experimental Group (using the developed AI learning module) and 1DAU as Control Group (using conventional learning module), were involved in analyze understanding of physic mechanics (pre-post test). Three sets of questionnaires were used as research instruments: 1) A survey questionnaire  likert scale measurement analyze the problems faced by students in terms of chapter assessment, course structure, teaching delivery, motivation, and quality learning. 2) Pre-test questionnaire aimed at measuring students' assessment before the treatment 3) Post-test questionnaire aimed at measuring students' assessment after the treatment. The Pre and Post test is multiple-choice questions (MCQ) covering chapters 1 to 7 syllabus of mechanic physic. The t-test data for Experimental-Control Group: pre-test t(58) = 0.824 and post test t(58) = 0.906. Result indicating  there is a significant difference, the experimental group scoring higher than the control group. The findings of the study indicated that there was an improvement in understanding those who used the AI learning module. This learning module has helped students enhance their understanding.